Upaya Meningkatkan Kemampuan Perencanaan Karir Melalui Layanan Informasi Dengan Penggunaan Media Audio Visual Pada Siswa Kelas XI SMK Kesehatan Borneo Bhakti Husada Palangka Raya - Lisah, Lisah; Sangalang, Merson U. (Universitas Palangka Raya, 2021)
Career planning is a process by which individuals can identify and take steps to achieve career goals. This study aims to determine the effectiveness of information services using Audio Visual Media to improve career planning in class XI students at SMK Kesehatan Borneo Bhakti Husada Palangka Raya. The research used was a true experimental study with a pretest-posttest control group design. The population of this study amounted to 37 (thirty seven) students with a sample of 12 (twelve) students determined by purposive sampling technique. Data collection techniques in this study used interviews, observations and questionnaires. The data analysis technique used paired T-test. From the results of the research that has been done, the pretest score is 56.5 and the posttest score is 81.5 with an increase in score of 25. This proves that there is an increase between pretest and posttest scores. From the results of the research that has been carried out the results of hypothesis testing using the paired t-test formula to prove the hypothesis at an error level of 0.05 if t count> ttable on db n-1 it is known that tcount = -68.465 and ttable = -2.571. This means that t count > t table, then Ho is rejected and Ha is accepted. These results indicate that information services with the use of audio visual media are effective for improving career planning for XI grade students of SMK Kesehatan Borneo Bhakti Husada Palangka Raya.